Bird diversity in the Mount Dempo area, South Sumatra: An ecological resource for local-based biology learning - Armanda, Fahmy; Wicaksono, Anggun; Oktiansyah, Rian (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2025)
Mount Dempo, South Sumatra, hosted a diverse range of bird species, making it a valuable ecological resource for local-based biology learning. This study aimed to document bird diversity in the region and to explore its potential for ecological education. The research was conducted in 2020 during the COVID-19 pandemic era. Data collection was carried out in the Mount Dempo area, limited to an altitude of approximately 2,086 meters above sea level at Shelter 1. The research employed the observation (point count) method along ecotourism routes by recording trails traversed using GPS. Sampling was conducted by walking along the path accompanied by predetermined observation points. The results recorded 21 bird species with a total of 96 individuals. The diversity analysis using the Shannon-Wiener Index produced a value of H' = 2.68, indicating moderate to high diversity, while the Simpson’s Index (D = 0.092) suggested very low species dominance. Additionally, the Evenness Index (E = 0.88) reflected a relatively even distribution of individuals among species, highlighting ecological stability in the study area. The presence of various ecological niches and bird functional groups supported the development of environmental literacy and conservation awareness among students. Thus, integrating local bird diversity as a contextual learning resource was considered a strategic approach to enhance ecological understanding and foster pro-environmental behavior among learners.